NUB1 Protein Regulates Cullins And E3 Ligases In Estrogen Receptor negative Breast Cancer - Tan Ka Liong; S. Haider; C. Zois; H. Turley; R. Leek; A. Harris; F. Buffa; O. Acuto; F. Pezzella (Elsevier Inc., 2024)
Volume 61, Supplement 1